Agility and coordination testing in hand-to-hand combat sports - Platonov, V.; Nikitenko, A. (Polish Journal of Sport and Tourism, 2019)
Introduction. The aim of the study is to analyse existing tests for assessing agility in combat sports and martial arts, as well as to develop new tests and to test their effectiveness. Material and methods. The study involved 16 athletes at various competitive levels specialising in hand-to-hand combat. It used the following methods: review of specialised literature along with policy and normative documents, an expert survey, testing, instrumental methods of assessing psychophysical capabilities, a pedagogical experiment, and methods of mathematical statistics. Results. The article clearly delineates the concepts of "agility" and "co-ordination". It was found that most of the exercise tests recommended for assessing agility actually only evaluate coordination, without taking into account unexpected and unpredictable situations, which are the key components of agility. While some tests allow for the assessment of agility, they are based on motor actions which are non-specific for combat sports. Moreover, the use of computer-based techniques for studying the visual-motor reaction has proven to be ineffective for assessing agility in sports. Conclusions. The article proposed three variants of specialised tests for assessing agility in motor actions specific for hand-to-hand combat. According to the results of all the three tests, the programme proposed for the development of agility and coordination caused a significant improvement in the level of agility in six months.